Right Ventricular Assessment in Critically Ill COVID-19 Patients and its Prognostic Importance - Mohamad, Yahia; El-Sherif, Rania; Adel Gawish, Mahmoud; Abdrabo, Ibrahim; Mowafy, Hatem Hossam (Open Access Macedonian Journal of Medical Sciences, 2022)
Background; Cardiac injury is a prevalent complication and is associated with worse prognosis in COVID-19 patients. The increased cardiac workload resulting from respiratory failure and hypoxemia is a common mechanism of cardiac injury and the right ventricle may bear the brunt of its impact. The aim of the present study was to determine the incidence and prognostic value of RV dysfunction in COVID-19 patients admitted to ICU using conventional echocardiography parameters.Patients were subjected to full history taking, and clinical examination, Computed Tomography of chest was done for all patients to assess severity of lung infiltration, all patients received standard treatment according to Ministry of Health and Population COVID19 treatment protocol recommendations. Echocardiographic assessment was done to all patients.The mean age of the patients was 61.10±9.64years (range 42-80years).There were 36 (60%) male and 24 (40%) female. The non-survivor group consisted of 28 patients (46.7%) and survivors consisted of 32 patients (53.3%). There was statistically significant association between mortality and RV function regarding TAPSE, FAC%, RV basal diameter and EPAP. We concluded that in COVID-19 patients, RV function must be assessed and its prognostic importance recognized. RV dysfunction is not only a symptom of high pulmonary pressures, but it also contributes to cardiac insufficiency.